2020
DOI: 10.1101/2020.05.30.20117952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological consequences of the Flint Water Crisis: A systematic review

Abstract: Given the COVID-19 outbreak, these unprecedented times pose many urgent dilemmas about how to support the mental health of communities. The goal of this research is to summarize existing literature on the mental health impact of the recent Flint Water Crisis. In March 2020, we searched five databases for literature exploring the psychological consequences of the crisis. Main findings were extracted. 132 citations were screened and eleven included in the review. Results suggest a negative psychological effect c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…11 Similar messaging has been repeated within the community for over six years (Roy et al, 2023 14 : Table S2), amidst reports of higher rates of depression, post-traumatic stress disorder, substance use, and other mental health problems in the general Flint population. [16][17][18][19][20][21][22][23][24] Beliefs about the effect of the FWC lead exposure on children's cognitive abilities cannot be reconciled with data on blood lead levels in Flint children. Research demonstrated that children's blood lead levels in Flint were not significantly different from the State average and were dramatically lower than children in neighboring Detroit.…”
Section: Introductionmentioning
confidence: 99%
“…11 Similar messaging has been repeated within the community for over six years (Roy et al, 2023 14 : Table S2), amidst reports of higher rates of depression, post-traumatic stress disorder, substance use, and other mental health problems in the general Flint population. [16][17][18][19][20][21][22][23][24] Beliefs about the effect of the FWC lead exposure on children's cognitive abilities cannot be reconciled with data on blood lead levels in Flint children. Research demonstrated that children's blood lead levels in Flint were not significantly different from the State average and were dramatically lower than children in neighboring Detroit.…”
Section: Introductionmentioning
confidence: 99%